There and Back Again - Current Cognitive Values of the Hippie Music - Marcin Michalak (Maria Curie-Skłodowska University, Lublin, Poland, 2019)
The aim of the article is a review of the musical output characterised as the "hippie one" in the context of its contemporary cognitive values. The retrospective of the bands, performers and pieces of music was preceded by a short description of the american and polish hippie movement of the sixties and the seventies of the 20th century. The review of the selected examples of the musical creativity of that period was conducted paying special attention to their musical, textual, visual (album covers, stage performances) values, also quoting creators` profiles as well as the socio-cultural background of the epoch. In the conclusion the author made an attempt at shifting the distinguished values of the hippie music onto the educational ground with references to the contemporary artistic, civic education, as well as - critical pedagogy or didactics of creativity.